Isolation and identification of AM Fungi associated with Phyllanthus species - and N. SUJATHA, L.R. GOJE, A. SHARMA (Indian Phytopathology, 2005)
Rhizosphere soil of Phyllanthus species was screened for isolation of Arbuscular mycorrhizal (AMF) propagules. 12 species were isolated belonging to four genera Acaulospora, Entrophosphora, Glomus and Sclerocytis.